Understanding the Phytoremediation Mechanisms of Potentially Toxic Elements: A Proteomic Overview of Recent Advances - Alsafran, Mohammed; Usman, Kamal; Ahmed, Bilal; Rizwan, Muhammad; Saleem, Muhammad Hamzah; Al Jabri, Hareb (Frontiers in Plant Science, 2022)
Potentially toxic elements (PTEs) such as cadmium (Cd), lead (Pb), chromium (Cr) and arsenic (As), polluting the environment, pose a significant risk and cause a wide array of plant diseases. These elements are non-biodegradable and prone to ascend along the food chain, making their environmental prevention a critical intervention. Current world initiatives to remove the toxicants are costly and might lead to more pollution. An emerging technology that may help in their removal is phytoremediation. Compared to traditional methods, phytoremediation is eco-friendly and less expensive. While many studies have reported several plants with high PTEs tolerance, uptake and then storage capacity in their roots, stem and leaves. However, the wide application of such a promising strategy still needs to be achieved, partly due to a poor understanding of the molecular mechanism controlling the phytoremediation process to optimize plants performance for large-scale field application. The aim of the present study to discuss the detailed mechanism/s behind that play a pivotal role to in uptake the PTEs from the polluted environment into plant’s body, then scavenge/detoxify and finally bioaccumulate the PTEs in different plant organs. Recently, interest in the comparative proteomics study of plants exposed to PTEs toxicity results in appreciable progress in this area. This article overviews the proteomics approach to elucidating the mechanisms underlying plants PTEs tolerance and bioaccumulation for optimized phytoremediation of polluted environments.